Caracterização morfométrica da microbacia hidrográfica do Córrego da fazenda glória, Município de Taquaritinga, SP. - Rodrigues, Flavia Mazzer [UNESP]; Pissarra, Teresa Cristina Tarlé [UNESP]; Campos, Sérgio [UNESP] (My University, 2008)
The analysis of morphometric characteristics is used to understand the relationship between soil and surface as a result of erosive processes on different structures and lithologies. The objective of this study was to study the morphometric characteristics of Fazenda Gloria watershed from 1983 to 2000, a fourth-order watershed in Taquaritinga Municipality, São Paulo State. The study was based on photointerpretation techniques. Drainage net and the respective watersheds were selected and the morphometric variables were determined. The watersheds consisted of 7 second-order watersheds and 2 third-order watersheds. The morphometric characteristics showed a reduction in the number of segments of first-order rivers and in the length of the drainage net during the study period. These findings could be related to several influences on land development considering occupation and use of land. A different hydrological behavior could also be observed. The analysis of Fazenda Glória Watershed showed that the length of the segment of fourth order river remained constant during the study period.
Morphometric characterization of Glória farm watershed, Taquarintinga, State of São Paulo, Brazil
Keywords: Morphometric analysis; Remote sensing; Watershed; Geomorphology; Hydrology; Lithology; Watersheds; drainage; hydrological response; land use; morphometry; remote sensing; soil erosion; watershed; Brazil; Sao Paulo [Brazil]; South America; Taquaritinga